Analysis of the Validity of Inter-Religious Marriages Held Abroad - PERMANA, Gede Esa Surya; SUJANA, I Nyoman; AGUNG, Anak Agung Istri (Indonesia Strategic Sustainability, 2024)
Purpose: Marriage according to the Marriage Law is valid if it is carried out according to the laws of each religion and its beliefs. Therefore, interfaith marriages are prohibited in Indonesia. Many couples of different religions who want to get married choose to get married abroad so that the marriage is considered valid by the state and has legal certainty.Methodology:The research method used is normative legal research, which uses primary and secondary legal sources and is then analyzed qualitatively using the deductive method.Findings: Normative legal certainty is generally seen from the validity of regulations made and enacted with certainty because they regulate clearly and logically. Marriages that take place abroad must be reported to the population and civil registration office according to the place of residence of the couple who are getting married, especially as the results of my interview as a researcher, the couple who got married abroad reported their marriage to the population and civil registration office in Bali, especially to the population and civil registration office of Badung Regency.Implication:A marriage conducted abroad is valid if it is conducted according to the laws in force in the country where the marriage is conducted and does not violate the provisions of the legal system in Indonesia. The marriage is considered valid in the legal system in Indonesia if it has been reported and recorded at the Population and Civil Registration Service, where the husband and wife who conducted the marriage abroad reside.